Treatment of Mycobacterium avium Complex (MAC) - Griffith, David E. (Seminars in Respiratory and Critical Care Medicine, 2018)
Mycobacterium avium complex (MAC) is the most commonly isolated nontuberculous mycobacterial respiratory pathogen worldwide. MAC lung disease is manifested either by fibrocavitary radiographic changes similar to pulmonary tuberculosis or by bronchiectasis with nodular and reticulonodular radiographic changes. This latter form of MAC lung disease, termed “nodular bronchiectatic (NB) MAC lung disease” is the most common form of MAC lung disease in the United States. Treatment at the time of diagnosis is always indicated for fibrocavitary MAC lung disease because it is always progressive and associated with increased morbidity and mortality compared with NB MAC lung disease. In contrast, the NB form of MAC lung disease is more indolent and frequently does not require antimycobacterial therapy. For patients with NB MAC lung disease, the priorities are typically to treat the underlying bronchiectasis and determine the course and impact of the MAC infection over time. Guidelines-based MAC therapy with multidrug regimens including macrolides is usually effective, but far from as predictably effective and durable as therapy for tuberculosis. It is imperative that clinicians are familiar with MAC drug resistance mechanisms and the pitfalls of inappropriate dependence on in vitro drug susceptibility testing which can predispose patients to the development of macrolide resistance with its attendant high mortality. It is now more than 20 years since the emergence of macrolides for MAC therapy with no new comparably effective agents introduced in that time, although one new inhaled amikacin therapy under study offers promise.
Keywords: Mycobacterium avium complex; treatment; mycobacteria; macrolide; bronchiectasis